Pengaruh Komunikasi Organisasi dan Disiplin Kerja terhadap Kinerja Karyawan pada Kedai Kopi Kulo Samarinda - Damaiyanti, Diah; Sanjaya, Arwin; Hetami, Adietya Arie (Indonesian Journal of Islamic Economics and Finance, 2021)
Each company aims to develop the company to its full potential. For goals to be achieved smoothly, leaders need to pay attention to the performance of their employees. The implementation of organizational communication and work discipline will help control all actions and behavior of employees to always comply with the provisions that have become company rules. This study aims to see the effect of communication and work discipline on employee performance at the Kulo coffee shop in Samarinda. Organizational Communication (X1) and Work Discipline (X2) are used as independent variables while Employee Performance (Y) is the dependent variable. The type of research used is quantitative research with a survey research design. The data analysis used multiple linear regression techniques using SPSS version 22. The population in this study were all employees of Kedai Kopi Kulo Samarinda who got 30 employees and the sampling method saturated 30 respondents. The results of this study can be variable communication variables Organization (X1) and Work Discipline (X2) together (simultaneously) have a significant effect on Employee Performance (Y) at the Kulo Coffee Shop in Samarinda. With the work result of 0.650 which is at the level of a strong relationship, the results of the determination are 42.3% of the Employee Performance variable (Y) and the results of the Fount 9.994> Fable 3.35 then Ho is rejected and Ha is accepted, namely between the Work Communication variable (X1) and Work Discipline. (X2) has a positive effect simultaneously on Employee Performance (Y). For the leadership of the Kulo Coffee Shop, they can open discussion forums for employees, such as briefings every time so that the aspirations given by the leadership can be well received by employees. employee discipline level can apply rewards and punishments.